Assessment of Pain During Endotracheal Suction In the Pediatric Intensive Care Unit - (:unkn) unknown (ELSEVIER SCIENCE INC, 2015)
This research was planned as a two-level definitive and comparative study to evaluate pain during endotracheal suction (ETS) in pediatric intensive care units (PICUs). This study was comprised of patients admitted to and the nurses working in the PICU. Cases were selected among PICU patients (N = 65) who met the study criteria and nurses (N = 18) who cared for them from January 1 to July 2, 2008. Routine ETS was applied as the first level of the study. For the second level, an inquiry on the knowledge of nurses about suction was given to the nurses, and they were asked to apply suction according to the guidelines they were given. All the obtained data were evaluated by statistical package for the social sciences (SPSS) for Windows 14.0. In summary, 33.8% (n = 22) of the patients were between ages 1 and 12 months, and 64.6% (n = 42) were boys. Although group 2 patients (patient who is in experimental group) had higher scores on the Wong-Baker faces pain rating and Face, Legs, Activity, Cry, Consolability scales, no statistical difference was found between the two groups (p > .05). Patients who received bolus doses of analgesia and sedative drugs had lower Wong-Baker faces pain rating (4.38 +/- 0.96; n = 4) and Face, Legs, Activity, Cry, Consolability scores (4.61 +/- 1.94; n = 4) (p >. 05). According to these findings, the patients were distressed because of the pain related with suction. Therefore, it is recommended that suction guidelines be used in PICUs during ETS. (C) 2015 by the American Society for Pain Management Nursing
Keywords: CLINICAL-PRACTICE; POSITION; INFANTS